2012
DOI: 10.1016/j.virol.2011.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and epidemic occurrence of enterovirus 68 respiratory infections in The Netherlands in 2010

Abstract: Following an increase in detection of enterovirus 68 (EV68) in community surveillance of respiratory infections in The Netherlands in 2010, epidemiological and virological analyses were performed to investigate the possible public health impact of EV68 infections. We retrospectively tested specimens collected from acute respiratory infections surveillance and through three children cohort studies conducted in The Netherlands from 1994 through 2010. A total of 71 of 13,310 (0.5%) specimens were positive for EV6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
218
4
14

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(262 citation statements)
references
References 38 publications
26
218
4
14
Order By: Relevance
“…EV-D68 was first isolated from children with respiratory infections in California in 1962 (3). It was long considered a rare pathogen, but the frequency of detecting EV-D68 during outbreaks of respiratory disease has increased (4,5) and over the past decades, three clades of EV-D68 (A, B, and C) have emerged and spread worldwide (6,7). EV-D68 infections mostly cause mild respiratory disease but can also result in severe bronchiolitis or pneumonia, especially among children (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EV-D68 was first isolated from children with respiratory infections in California in 1962 (3). It was long considered a rare pathogen, but the frequency of detecting EV-D68 during outbreaks of respiratory disease has increased (4,5) and over the past decades, three clades of EV-D68 (A, B, and C) have emerged and spread worldwide (6,7). EV-D68 infections mostly cause mild respiratory disease but can also result in severe bronchiolitis or pneumonia, especially among children (4,5).…”
mentioning
confidence: 99%
“…It was long considered a rare pathogen, but the frequency of detecting EV-D68 during outbreaks of respiratory disease has increased (4,5) and over the past decades, three clades of EV-D68 (A, B, and C) have emerged and spread worldwide (6,7). EV-D68 infections mostly cause mild respiratory disease but can also result in severe bronchiolitis or pneumonia, especially among children (4,5). In 2014, a nationwide EV-D68 outbreak in the United States was associated with severe respiratory disease and a cluster of acute flaccid myelitis and cranial nerve dysfunction in children, implicating EV-D68 as an emerging public health threat (8,9).…”
mentioning
confidence: 99%
“…According to our previous reports, most of the EV68 strains detected in the Philippines belonged to lineage 2, and a few of them belonged to lineage 3 (4,10). The VP1 sequences detected in the Philippines and other countries demonstrated that the amino acid sequence patterns in BC and DE loops were correlated with the categorization of EV68 into the 3 lineages (6,8,10). Generally, loop structures, including BC and DE loops, are located on the viral surface and associated with antigenic epitopes of enteroviruses (11,12).…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 76%
“…In an enterovirus surveillance conducted in the United States from 1970 to 2005, only a total of 26 strains were reported over 35 years (2). However, the number of reported EV68 cases increased dramatically in the late 2000s, in different parts of the world (3)(4)(5)(6)(7)(8). The underlying molecular mechanism for this sudden increase of EV68 detections in recent years is still unknown.…”
Section: H Uman Enterovirus 68 (Ev68) (Species Human Enterovirus D;mentioning
confidence: 99%
See 1 more Smart Citation